Rekrutmen Private Military Contractors Yang Dilakukan Negara Dibolehkan Dalam Hukum Internasional - Yusuf, Rifadli Mahram; Wattimena, Josina Augustina Yvonne; Tahamata, Lucia Charlota Octovina (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: Private Military Contractors (PMC) are former military personnel employed by private military companies or what are known as Private Military Companies/Private Military Contractors (PMC). The widespread use of military contractors in armed conflicts such as the one in Iraq has raised problems in international law, especially international humanitarian law related to the use of military contractors. The involvement of its members in armed conflicts often results in unclear status in International Humanitarian Law, with many assuming that PMCs are the same as paid soldiers.Purposes of the Research: The aim of the research is to determine the legal status of PMSCs in the invasion of Iraq by the United States (US) based on applicable international law and to analyze the responsibility of the United States (US) as the party that used PMCs in the invasion of Iraq which has caused many problems for Iraq.Methods of the Research: The research method used is normative juridical using a case approach, conceptual approach and statutory approach.Results of the Research: The results of this research show that the legal status of mercenaries is legally recognized in accordance with the 1949 Geneva Convention and confirmed in Additional Protocol 1 of 1977 Article 47 paragraph (1) that: "A mercenary is not entitled to the status of a combatant or prisoner of war" and Sanctions which can be applied in violations of International Law, namely, Complaint, Reprisal, and Payment of Compensation or Compensation.